The Prosecutor's Authority to Conduct Investigations into Corruption Crimes Causing State Financial Losses (Case Study in PT. Timah Tbk) - Iskandar, Indra; Siregar, Hamdan Azhar (Law Development Journal, 2025)
The performance of the prosecutor's office in eradicating corruption is seen in the case of PT. Timah Tbk. Starting from the alleged corruption of the tin commodity trade system in the Mining Business Permit (IUP) area of PT Timah Tbk for 2015-2022, where the total loss reached IDR 271 trillion. In the process of enforcing the law on corruption in Indonesia, there are investigators from three institutions established by the state in their capacity as law enforcement officers who have been given authority to each investigator through law. The authority of investigation by the prosecutor's office is regulated in Law 16 of 2004 in conjunction with Law No. 11 of 2021 concerning Amendments to Law No. 16 of 2004 concerning the Attorney General's Office of the Republic of Indonesia. Based on the decision of the Constitutional Court No. 28/PUU-V/2007 states that Article 30 paragraph (1) letter d of the Prosecutor's Office Law which gives the Prosecutor's Office authority other than prosecution, namely to conduct investigations, does not necessarily contradict the 1945 Constitution. Investigations carried out by the Prosecutor's Office are crimes that are difficult to resolve, such as corruption. The obstacles encountered by prosecutors in investigations are the authority held by investigators as regulated in Article 5 paragraph (1) of the Criminal Procedure Code, namely to seek information and evidence. At this stage, investigators must be as capable as possible of seeking and finding assets belonging to perpetrators of corruption.